Pengaruh Suhu Proses Karbonasi Terhadap Konduktivitas Listrik Arang Bambu Sebagai Elektroda Superkapasitor - Messy Shania Pongajow; Heinrich Taunaumang; Farly R. Tumimomor; Alfrie M. Rampengan (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
. Electrical energy is a primary need for every human being. Supercapacitors are sophisticated electrical energy storage devices that combine the advantages of conventional batteries and capacitors so that they have the ability to store energy better. The use of electrode materials is one of the factors that affect the effectiveness of supercapacitors, electrode materials can be made from polymeric materials, metal oxides, and porous materials such as activated carbon. Activated carbon is made through two main stages, namely the carbonization and activation stages. Bamboo charcoal is a solid product that uses bamboo raw materials through a carbonization process under high temperatures (high temperature charcoal). This research is a research using experimental method. From the research results, carbonized bamboo charcoal at temperatures of 300˚C, 350˚C, 400˚C, 450˚C and 500˚C has a higher electrical conductivity value as the carbonization temperature increases. So it can be concluded that the temperature in the carbonization process affects the electrical conductivity of bamboo charcoal.